Indonesian University Students' Perception on Instructor-Initiated Writing Activities - Laode Muhammad Firman Guntur; Sadegh Rahimi Pordanjani (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2019)
The recent literature of writing studies suggests that there is a possibility of different perception between instructor and university students on what causes students’ writing reluctance which leads to ineffective writing teaching activities initiated by the instructor. Such ineffective teaching has, then, become the main cause of students’ disengagement in writing classes at university. This paper is aimed at exploring the perception from students’ side as the targeted individuals within the teaching process itself. In order to describe such perception, a critical literary review of previous studies from the relevant area is employed. It is argued that students’ perception on instructor-initiated writing activities are influenced by pedagogical consequences, learner’s linguistic competence, and their original perceptions of the English writing skill. This investigation has found that it is very crucial for instructors to design activities that engage students in three dimensions: cognitive, behavioural, and emotional. The study also finds that instructors' selection of teaching strategies influences students' motivation extrinsically in the form of reinforcement, or in contrast, degradation of their motivation. Finally, this study confirms it is possible for students to respond pedagogical activities differently from the expectation of the instructors.